2007
DOI: 10.4049/jimmunol.178.4.2212
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Tolerance Induction Using Ethylenecarbodiimide-Fixed APCs Uses both Direct and Indirect Mechanisms of Antigen Presentation for Prevention of Experimental Autoimmune Encephalomyelitis

Abstract: MHC class II (MHC II)-restricted T cell responses are a common driving force of autoimmune disease. Accordingly, numerous therapeutic strategies target CD4+ T cells with the hope of attenuating autoimmune responses and restoring self-tolerance. We have previously reported that i.v. treatment with Ag-pulsed, ethylenecarbodiimide (ECDI)-fixed splenocytes (Ag-SPs) is an efficient protocol to induce Ag-specific tolerance for prevention and treatment of experimental autoimmune encephalomyelitis (EAE). Ag-SPs couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 43 publications
4
142
0
Order By: Relevance
“…Recent studies indicate that ECDI treatment induces the cells to undergo rapid apoptosis and that tolerance is induced by both direct and indirect antigen presentation (18). Cell tracking indicates that ECDI-treated cells distribute widely, but intact cells disappear within 48 hours (S.D.M., unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that ECDI treatment induces the cells to undergo rapid apoptosis and that tolerance is induced by both direct and indirect antigen presentation (18). Cell tracking indicates that ECDI-treated cells distribute widely, but intact cells disappear within 48 hours (S.D.M., unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…infusion of ECDI-treated donor splenocytes induced indefinite donor-specific tolerance in allogeneic islet cell transplantation. Here, the antigens of interest are mainly donor MHC class I and II molecules that are an integral surface component of donor lymphocytes, and ECDI treatment presumably interferes with costimulatory signals leading to tolerance induction to the membrane-bound allogeneic MHC antigens (18,19). Two previous studies examined the efficacy of ECDI-treated donor dendritic cells or whole splenocytes in full MHC-mismatched heart and skin transplant models (20,21).…”
mentioning
confidence: 99%
“…Manipulation of T cell activation and differentiation pathways has been at the center of current tolerance induction theory, and the basis of tolerance induction utilizing current immunosuppressive agents. Over recent years, experimental models have shown that it is possible to exploit the mechanisms that normally maintain immune homeostasis and tolerance to self-antigens, as well as to reintroduce tolerance to self-antigen in an autoimmune setting (Getts et al, 2011;Kohm et al, 2005;Podojil et al, 2008;Turley and Miller, 2007). However, in the clinical setting the utilization of co-stimulatory blockade, soluble peptide, altered peptide ligands among others have yielded disappointing results.…”
Section: Current Clinical Strategies In Multiple Sclerosis To Modifymentioning
confidence: 99%
“…While there is clear evidence for the role of T cell anergy in Ag-ECDI-SP tolerance, subsequent studies have shown that splenocytes treated with antigen-processing inhibitors, MHC knock-out splenocytes, or donor red blood cells (RBCs) lacking MHC class II expression can still induce tolerance [16,23,24]. This suggests that T cell anergy through direct TCR engagement of the Ag-ECDI-SP is not required, rather tolerance induction is primarily achieved through indirect mechanisms involving host antigen-presenting cells (APCs)…”
Section: Mechanism Of Ag-ecdi-sp Tolerancementioning
confidence: 99%